Impact of Distributor ROI on the Territory Operation of FMCG Companies - Hussain, Mohammed Arif (Digital Repository of Theses - SSBM Geneva, 2025)
The efficiency of territory operations in Fast-Moving Consumer Goods (FMCG) companies is closely linked to the profitability and sustainability of their distribution networks. Distributor Return on Investment (ROI) serves as a critical metric in evaluating distributor performance, influencing market expansion, product availability, and overall sales effectiveness. This study examines the impact of distributor ROI on territory operations using secondary data sources, including financial reports, industry analyses, and market performance metrics. By analyzing existing data from FMCG companies, distributor financial statements, and market research reports, this study identifies key factors affecting distributor profitability, such as trade margins, operating costs, sales volume, and competitive dynamics. The findings reveal significant correlations between distributor ROI and market coverage efficiency, stock availability, and supply chain responsiveness. Furthermore, the study highlights challenges distributors face, including fluctuating demand, credit policies, and pricing pressures, which can impact their ROI and, in turn, the operational efficiency of FMCG companies in different territories. The research provides strategic insights for FMCG firms to optimize distributor ROI through better incentive structures, cost management strategies, and supply chain enhancements. By leveraging data-driven approaches, companies can improve distributor relationships, enhance market penetration, and drive long-term business sustainability. Keywords. Distributor ROI, FMCG, Territory Operations, Secondary Data Analysis, Market Efficiency, Supply Chain